Analisis Sanksi Tindak Pidana Pelaku Kelalaian Dalam Berkendara Mengakibatkan Kematian Dalam Putusan Nomor: 313/Pid.Sus/2024/Pn Jmr Perspektif Hukum Pidana Islam - Irfan Fadil, Muhammad; Azazy, Yusup; Rozikin, Opik (Maqasid: Jurnal Studi Hukum Islam, 2025)
This study is motivated by the differences in the application of sanctions between positive law and Islamic criminal law for perpetrators of traffic accidents resulting in death due to negligence. The main issue in this study is the discrepancy between the types of sanctions imposed by judges in the positive legal system and those recommended by Islamic criminal law. The purpose of this research is to analyze and compare the forms of accountability applied to perpetrators under both legal systems and to evaluate the implications of justice for both victims and offenders. The method used is normative juridical with a conceptual and case approach. Data were obtained through literature study of court decisions and relevant scholarly works, followed by qualitative analysis of the sanction concepts in both legal systems. The findings indicate that sanctions under positive law tend to emphasize imprisonment, even when the act is committed due to negligence. In contrast, Islamic criminal law classifies such acts as unintentional offenses that are not punishable by imprisonment, but rather require financial compensation to the victim’s family and moral redemption by the offender. This approach is considered to prioritize restorative justice values and the restoration of social relationships. This research recommends the integration of restorative justice principles into the criminal justice system, particularly in cases involving unintentional acts, in order to achieve a more proportional and humane form of justice. Keywords: Accident, Negligence, Islamic Criminal Law, Sanction, Diyat